Twenty steps towards an adequate inferential interpretation of p-values - Hirschauer, Norbert; Grüner, Sven; Mußhoff, Oliver; Becker, Claudia (PeerJ Preprints, 2018)
We suggest twenty immediately actionable steps to reduce widespread inferential errors related to “statistical significance testing.” Our propositions refer first to the theoretical preconditions for using p-values. They furthermore include wording guidelines as well as structural and operative advice of how to present results, especially in multiple regression analysis. Our propositions aim at fostering the logical consistency of inferential arguments by avoiding false categorical reasoning. They are not aimed at dispensing with p-values or completely replacing frequentist approaches by Bayesian statistics.
Keywords: statistical inference; p-value